TEACHING NON-BINARY ANTONYM THROUGH CARD GAME STRATEGY TO THE SEVENTH GRADE STUDENTS - Joko Priyono Saputro (Universitas PGRI Palembang, 2019)
Abstarct: The main problem of this research was â€œIs it effective to use card game in teaching non-binary antonym for the seventh grade students of SMP Negeri 08 Prabumulih?â€ Therefore, the objective of this research was to find out whether or not it is effective to use card game in teaching non-binary antonym for the seventh grade students of SMP Negeri 08 Prabumulih. The true experimental method was used in this research. The writers collected data from the seventh grade students of SMP Negeri 08 Prabumulih with the population of 175 students, 70 students were taken through cluster random sampling procedure, in the sense that there were two classes randomly chosen as the sample. One class was the experimental group and the other class was the control group. To collect data, a written test was used. The analysis data was done by using the matched t-test. Â Based on the result of the data analysis, it showed that the result of the matched t-test calculation was 6.090 and the critical value of t-table at 5% of significance level with df = 28 (29-1) was 1.701. It means that t-obt was higher than t-table, meaning that null hyphotheses (Ho) was rejected and alternative hyphotheses (Ha) was accepted. In conclusion, it was effective to apply the card game in teaching non-binary antonyms to the seventh grade students of SMP Negeri 08 Prabumulih.Â